Elevated intracranial pressure causes optic nerve and retinal ganglion cell degeneration in mice. (July 2015) - Nusbaum, Derek M.; Wu, Samuel M.; Frankfort, Benjamin J.
Abstract: The purpose of this study was to develop a novel experimental system for the modulation and measurement of intracranial pressure (ICP), and to use this system to assess the impact of elevated ICP on the optic nerve and retinal ganglion cells (RGCs) in CD1 mice. This system involved surgical implantation of an infusion cannula and a radiowave based pressure monitoring probe through the skull and into the subarachnoid space. The infusion cannula was used to increase ICP, which was measured by the probe and transmitted to a nearby receiver. The system provided robust and consistent ICP waveforms, was well tolerated, and was stable over time. ICP was elevated to approximately 30 mmHg for one week, after which we assessed changes in optic nerve structure with transmission electron microscopy in cross section and RGC numbers with antibody staining in retinal flat mounts. ICP elevation resulted in optic nerve axonal loss and disorganization, as well as RGC soma loss. We conclude that the controlled manipulation of ICP in active, awake mice is possible, despite their small size. Furthermore, ICP elevation results in visual system phenotypes of optic nerve and RGC degeneration, suggesting that this model can be used to study the impact of ICP on the visual system. Potentially, this model can also be used to study the relationship between ICP and IOP, as well diseases impacted by ICP variation such as glaucoma, idiopathic intracranial hypertension, and the spaceflight-related visual impairment intracranial pressure syndrome. Highlights: We developed a novel system with which to measure and modulate intracranial pressure in mice. We studied mice exposed to elevated intracranial pressure for one week. We examined changes in optic nerve appearance and retinal ganglion cell number. After intracranial pressure elevation, optic nerve axon and retinal ganglion cell soma loss were prominent.